Why Does the Genre of the Gospels Matter?: The Gospels’ Genre and Historical Jesus Research - Vytlačilová, Magdalena (The catholic biblical quarterly, 2025)
The primary aim of this study is to assess whether the contemporary consensus on the genre of the Gospels has contributed to a deeper understanding of early Christianity and the historical Jesus. I demonstrate that many modern scholars tend to understand the classification of the Gospels as biographies only as a matter of taxonomy, overlooking the broader implications of this perspective, namely, for areas such as the purpose of the Gospels, study of Jesus’s self-understanding, and chronology of his life.